Microbial beta glucosidase enzymes - Srivastava, Neha; Rathour, Rishabh; Jha, Sonam; Pandey, Karan; Srivastava, Manish; Thakur, Vijay Kumar; Sengar, Rakesh Singh; Gupta, Vijai K.; Mazumder, Pranab Behari; Khan, Ahamad Faiz; Mishra, Pradeep Kumar (MDPI AG, 2019)
The biomass to biofuels production process is green, sustainable, and an advanced technique to resolve the current environmental issues generated from fossil fuels. The production of biofuels from biomass is an enzyme mediated process, wherein β-glucosidase (BGL) enzymes play a key role in biomass hydrolysis by producing monomeric sugars from cellulose-based oligosaccharides. However, the production and availability of these enzymes realize their major role to increase the overall production cost of biomass to biofuels production technology. Therefore, the present review is focused on evaluating the production and efficiency of β-glucosidase enzymes in the bioconversion of cellulosic biomass for biofuel production at an industrial scale, providing its mechanism and classification. The application of BGL enzymes in the biomass conversion process has been discussed along with the recent developments and existing issues. Moreover, the production and development of microbial BGL enzymes have been explained in detail, along with the recent advancements made in the field. Finally, current hurdles and future suggestions have been provided for the future developments. This review is likely to set a benchmark in the area of cost effective BGL enzyme production, specifically in the biorefinery area.
Recent advances in biomass conversation for biofuels application
Keywords: Cellulase enzyme; Enzymatic hydrolysis; Lignocellulosic biomass; β-glucosidase